Photoinduced absorption and anomalous dichroism in NaCa2Mn2V3O12 garnet as an evidence for the formation of oxygen holes dynamics - Eremenko, V.V.; Gnatchenko, S.L.; Kachur, I.S.; Piryatinskaya, V.G.; Ratner, A.M.; Shapiro, V.V.; Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
It is shown that long-lived photoinduced dichroism in garnets is caused by photoproduced charges with anisotropic structure, keeping long memory of the pumping light polarization, while photoinduced absorption is due to all photoproduced charges irrespective of their intrinsic structure. The charges with anisotropic structure are identified as two-center oxygen holes. The formation of an oxygen hole is preceded by the excitation of a charge-transfer state with electron partially transferred to a cation C (V5+ for NaCa2Mn2V3O12 garnet) from an adjacent oxygen anion. To turn this excited state into a free hole state requires some time thole during which the hole axis can be reoriented resulting in a diminution of dichroism. The time thole shortens with increasing ionization potential of the cation C (very high for V5+). Such a mechanism explains qualitatively a set of unusual experimental facts, in particular, a very strong dichroism observed just in the NaCa2Mn2V3O12 garnet, where photoinduced changes of all optical properties disappear after switching off of the irradiation significantly faster than those in other garnets examined.